Secure and Trust Computing, Data Management and Applications 8th FIRA International Conference, STA 2011, Loutraki, Greece, June 28-30, 2011. Proceedings - Park, James J.; Lopez, Javier; Yeo, Sang-Soo; Shon, Taeshik; Taniar, David (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the 8th FIRA International Conference on Secure and Trust Computing, Data Management, and Applications, STA 2011, held in Loutraki, Greece, in June 2011. STA 2011 is the first conference after the merger of the successful SSDU, UbiSec, and TRUST symposium series previously held from 2006 until 2010 in various locations. The 29 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers address various theories and practical applications of secure and trust computing and data management in future environments.